APPLICATION OF MSC ADAMS – NX NASTRAN/FEMAP INTERFACE IN STRENGTH CALCULATIONS OF TRUCK FRAMES - Adam PRZEMYK; Andrzej HARLECKI; Tomasz GANCARCZYK (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
In this paper, the finite element method (FEM) is used to calculate the strength of truck frames by integrating the MSC Adams software, for dynamics analysis of mechanical systems, and the NX Nastran/Femap software. At the same time, a method for reducing degrees of freedom is been developed based on the Craig–Bampton method. The interface is applied in order to calculate the strength of the frame in the selected truck, which runs on the test track. The selected model of truck can be treated as the virtual prototype that is useful in the design process.